Bi-functional particles for real-time phagosome acidification and proteolysis multiplex assay in macrophages - Méndez-Alejandre, Alba; Raymond, Benjamin Bernard Armando; Trost, Matthias; Marín-Rubio, José Luis (Frontiers in Immunology, 2023)
Phagosome acidification and proteolysis are essential processes in the immune response to contain and eliminate pathogens. In recent years, there has been an increased desire for a rapid and accurate method of assessing these processes in real-time. Here, we outline the development of a multiplexed assay that allows simultaneous monitoring of phagosome acidification and proteolysis in the same sample using silica beads conjugated to pHrodo and DQ BSA. We describe in detail how to prepare the bi-functional particles and show proof of concept using differentially activated macrophages. This multiplexed spectrophotometric assay allows rapid and accurate assessment of phagosome acidification and proteolysis in real-time and could provide valuable information for understanding the immune response to pathogen invasion.